NuGinga: a JavaScript Driven Implementation of Brazilian Digital TV Middleware for Android - Braga, Rodrigo; Klehm, Volnei; Santana, Leonardo; Takano, Kevin; Gama, Lauro; Lima, Addison; Melo, Vinícius; Paiva, Taynara; Gonzalez, Diego; Melo, Michael; Lee, Chak; Nascimento, Lois (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
All over the world, analog TV systems are being replaced by digital schemes, which, besides having better image and sound quality, can provide user interaction via an interactivity middleware. NuGinga is a web driven solution of the Ginga-NCL standard adopted in Brazil and other countries in South America, delivered on some digital TV capable devices from Latin America since the beginning of 2018. This paper intends to give an overall architecture description of NuGinga solution, a brief resume of some other solutions, and why developers have chosen such approach.